The effect of hydrogen diffusivities on PANI-modified epoxy coating under potentiostatic charging - Rahman, N.A.A. (Asian Research Publishing Network, 2016)
Underground pipelines are susceptible to physical degradation due to the effects of hydrogen permeation which can lead to metallurgical damages, which in turn will affect the service quality. This study employs the use of electrochemical technique to analyze the effects of hydrogen diffusion coefficient on carbon steel coated with Polyaniline (PANI) -modified epoxy in soil solutions at different potentiostatic charging conditions. The protective behavior of PANI-modified epoxy was investigated using adhesion test, hydrogen permeation test and potentiodynamic polarization measurement. The hydrogen diffusion coefficient was determined by the time lag method. The results from these experiments suggest that PANI-modified epoxy is a considerable option for hydrogen barrier coating for steel pipelines in soil environments at certain charging potential. Â© 2006-2016 Asian Research Publishing Network (ARPN).